What do people with type 2 diabetes want from a brief messaging system to support medication adherence? - Bartlett, Yvonne Kiera (Patient Prefer Adherence, 2019)
BACKGROUND: Many people with type 2 diabetes do not take their treatment as prescribed. Brief messages to support medication use could reach large numbers of people at a very low cost per person, but current interventions using brief messages rarely adequately describe the content of the messages, nor base these messages on explicit behavior change principles. This study reports the views of people with type 2 diabetes concerning the acceptability of 1) a messaging system and 2) proposed messages based on behavior change techniques (BCTs) and beliefs and concerns around taking medication. METHODS: The proposed system and brief messages were discussed in focus groups of people with type 2 diabetes recruited through general practices in England. Transcripts were analyzed thematically. PARTICIPANTS: Twenty-three participants took part in one of five focus group discussions. All participants were over 18 years, were taking tablet medication for their diabetes, and had access to a mobile phone. Key exclusion criteria were recent hospitalization for hyper- or hypoglycemia or diagnosis with a terminal illness. RESULTS: Four themes were identified as relating to the acceptability of the messaging system: “opportunities and limitations of technology”, “us and them (who is the system for?)”, “responsibility for adherence”, and “diabetes management beyond medication”. Participants recognized the benefit of using technology. Those with high confidence in their ability to adhere were keen to make a distinction between themselves and those who did not adhere; participants were more comfortable taking responsibility for medication than diet and exercise. Acceptability of the messages hinged on avoiding “preaching to the converted”. CONCLUSIONS: These findings show that brief messaging could be acceptable to the target population for a range of diabetes-related behaviors but highlight the need for such a system to be perceived as personally relevant. Acceptable messages would need to maintain novelty for the target population.